Reviewing Sabbath Rest as biblical and missional incentive to God’s rest: A reformation study - Takalani A. Muswubi (Verbum et Ecclesia)
This article reviews Sabbath Rest as the biblical and missional incentive towards God’s rest. The relationship between human restlessness and the Sabbath Rest is still one of the most serious, sensitive, contentious, controversial and debatable issues. Many scholars are still discussing this relationship, given the spiritual, psychological and physical effects of human ‘restlessness’ that characterise our technologically advanced, secularised, consumerist and commercialised-driven society. This article seeks to answer the question: to what extent does our conception (understanding) of the Sabbath Rest helps us address human restlessness? In this regard, this article reviews the concept of ‘Sabbath Rest’ within the Reformation framework, whereby three things are discussed, firstly, its formation period (direction), whereby God created the Sabbath Rest as signpost of and for God’s Rest before the fall of human beings into sin; secondly, its deformation period (misdirection), whereby the God-given Sabbath Rest commands uncover human restlessness after the fall of human beings into sin and lastly, but not the least, its reformation period (redirection), which is characterised by the two distinct periods, namely, the period of Christ’s first coming and the second period as the future coming of Christ.